Diuretic Effectiveness Test and Thin Layer Chromatography (TLC) Profile of Ethanol Extract of Brazilian Spinach Leaves (Althernanthera sisso hort) - Widhiastuti, Christina Dwi; Pratimasari, Diah; Amin, Muhammad Saiful (UNIB PRESS, 2024)
Hypertension is one of the diseases with the highest prevalence in the world. The group of hypertension drugs that are often used are diuretics. Brazilian spinach is a plant that has the potential to be developed as a diuretic. It is suspected that the contents of Brazilian spinach leaves used as a diuretic are alkaloids, flavonoids and saponins. This study aims to determine the presence of flavonoids and the diuretic effect of ethanol extract of Brazilian spinach leaves as a diuretic in male white rats. The research method is laboratory experimental and descriptive. Phytochemical screening includes alkaloids, phenolics, flavonoids, saponins, tannins, steroids/triterpenoids. Confirmation of the content of flavonoid compounds using the Thin Layer Chromatography (TLC) method. The subjects were 25 male white rats, divided into 5 groups. Positive control group, negative control, Brazilian spinach ethanol extract with 156.25 mg, 312.5 mg, and 625 mg. Rat urine volume was measured at 1-6 hours, pH, diuresis latency. The research results showed that the ethanol extract of Brazilian spinach leaves contained alkaloids, phenolics, flavonoids, tannins, saponins and steroids. Statistically, giving ethanol extract of Brazilian spinach leaves has a good diuretic effect at a dose of 625 mg/200gBW because the significant value shows P<0.05 or there is a difference